Chasing shadow and make believe - Mofokeng, Reikanne (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2018)
My thesis is a science fiction novella. It follows the story of an adolescent boy, Shadow, and a little girl, Makebelieve, in an ahistorical future. The world that they traverse is earth, after being nursed back to health, by technologically advanced Southern African societies. A series of inexplicable astronomical events leads to their being hunted down. Through the travels of Shadow and Makebelieve I show how the world and the societies around them operate. I am inspired by Samuel R Delaney's Aye, Gomorrah and Derrick Bell's The Space Traders, because of their prowess in world building and exploration of complex and innovative ideas.
Keywords: Creative writing (Higher education) -- South Africa; South African fiction (English) -- 21st century; Science fiction, South African (English) -- 21st century